EVALUATION OF MOTOR DEVELOPMENT OF BABIES WITH DOWN SYNDROME (Fiep Bulletin - online, 2012)
The child is a developing organism whose growth is expressed by behaviors or ways of doing things, ranging from simple reflex to voluntary act, this is due to progressive structuring of the CNS. It is known that in syndromic children, this maturation occurs later, causing a delay in the loss of primitive reflexes and reactions, which consequently lead to a delay in development areas. Therefore, the stimulation is of paramount importance since the first months of life. The aim of this study was to evaluate the motor development of infants (3-36 months) with Down syndrome. It is a descriptive and diagnostic APAE with 6 children - Parents and Friends of Exceptional Sunbeam Lages - SC 6 children, 1 female and 5 male. The children were assessed using the Psychomotor Development Scale Early Childhood Lezine and Brunet (1981) which assesses four areas of infant motor development, resulting in chronological age (CA), age of development (ID), negative age (IN) development and the ratios (DR) in the areas of posture (P), oculomotor (O), language (L), socialization (S) and global (G). The results were tabulated on an SIMODE, developed for this scale by Souza and Rosa Neto (2002), with the final result of a low normal range, 10 to 19 lower much lower in these areas. After data analysis it was concluded that infants with Down syndrome have deficits in all areas of development, with greater deficits in language and socialization, became evident the need for early intervention and stimulation to enable them to develop their skills not so late.
Keywords: Motor Development; Down syndrome babies; Brunet and Lezine.